Research in personnel and human resources management. Vol. 25 - Martocchio, Joseph J. (Emerald, 2006)
This series publishes monograph length conceptual papers designed to promote theory and research on important substantive and methodological topics in the field of human resources management. Volume 25 of "Research in Personnel and Human Resources Management" (RPHRM) contains eight papers on critical issues in the field of human resources management, thus continuing the tradition of the series to develop a more informed understanding of the field. This work offers an international representation and cutting edge papers that help to define the field of HRM.
Keywords: Business & Economics -- Human Resources & Personnel Management.; Personnel & human resources management.; Personnel management.; elektronické knihy; electronic books